Diversity, Distribution and Quantification of Antibiotic Resistance Genes in Goat and Lamb Slaughterhouse Surfaces and Meat Products - Lavilla Lerma, Leyre (PLoS One, 2014)
The distribution and quantification of tetracycline, sulfonamide and beta-lactam resistance genes were assessed in slaughterhouse zones throughout meat chain production and the meat products; this study represents the first to report quantitatively monitor antibiotic resistance genes (ARG) in goat and lamb slaughterhouse using a culture independent approach, since most studies focused on individual bacterial species and their specific resistance types. Quantitative PCR (qPCR) revealed a high prevalence of tetracycline resistance genes tetA and tetB in almost all slaughterhouse zones. Sulfonamide resistance genes were largely distributed, while beta-lactam resistance genes were less predominant. Statistical analysis revealed that resistant bacteria, in most cases, were spread by the same route in almost all slaughterhouse zones, except for tetB, bla(CTX) and bla(TEM) genes, which occurred in few zones as isolated ‘hot spots.’ The sum of all analyzed ARG indicated that slaughterhouse surfaces and end products act as reservoirs of ARG, mainly tet genes, which were more prevalent in slaughtering room (SR), cutting room (CR) and commercial meat products (MP). Resistance gene patterns suggest they were disseminated throughout slaughterhouse zones being also detected in commercial meat products, with significant correlations between different sampling zones/end products and total resistance in SR, CR and white room (WR) zones, and also refrigerator 4 (F4) and MP were observed. Strategically controlling key zones in slaughterhouse (SR, CR and WR) by adequate disinfection methods could strategically reduce the risks of ARG transmission and minimize the issues of food safety and environment contamination.